Outline on selected properties of densified veneers and the produced plywood - SALCA MANEA Emilia-Adela; BEKHTA Pavlo (Journal of Physics Conference Series, 2024)
Wood densification is one of the methods used to modify its properties to create a material with an increased density and implicitly improved properties. Generally, densification is applied to low-density and fast-growing wood species. Lower pressures and temperatures are applied for shorter time spans to densify veneers when compared to solid wood. Along with their increased strength, hardness, and durability, densified veneers present an attractive dark colour, a smooth surface, improved gloss, and higher thermal conductivity. There is a special interest in densified veneers for plywood production. These products present increased dimensional stability, higher strength properties, and a pleasant appearance having various applications. The present paper revises selected properties of densified veneers made of black alder wood species and the mechanical properties of plywood when produced from them.